3D Joint Density Mapping - Drews, Michael (Conference Proceedings, 2008)

A normal-faulting stress regime in the Bavarian Foreland Molasse Basin? New evidence from detailed analysis of leak-off and formation integrity tests in the greater Munich area, SE-Germany - Drews, Michael; Seithel, Robin; Savvatis, Alexandros; Kohl, Thomas; Stollhofen, Harald (Tectonophysics, 2019)
Leak-off and formation integrity test data from the central part of the Bavarian Foreland Molasse Basin have been investigated in detail to infer information about the stress regime of the Cenozoic basin fill. The detailed analysis of leak-off test data from the Bavarian Foreland Molasse Basin and lithology-dependent analysis of leak-off test and formation integrity data is the first of its kind in a published study. Only test data from shale-rich sequences have been considered. All data yield minimum principal stresses that are smaller than an estimated vertical stress range. In combination with critical stress and frictional equilibrium theory, the data indicate that the stress regime in the greater Munich area and possibly the far-field stress regime of the Bavarian Foreland Molasse Basin are most likely of an extensional nature (normal-faulting stress regime). Under the assumption of frictional equilibrium, a friction coefficient between 0.2 and 0.4 best explains failure in shale-dominated sections of the central part of the Bavarian Foreland Molasse Basin and can be used to estimate the minimum horizontal stress SHmin. However, even in the spatially restricted domain of the greater Munich area the stress regime might vary towards a strike-slip stress regime; most likely in the vicinity of fault zones and/or due to variations in mechanical rock strength. The results of this study have great impact and relevance to improved planning of drilling campaigns, future numerical modelling and the general understanding of the evolution of the Bavarian Foreland Molasse Basin. Additional leak-off tests and extended leak-off tests are recommended to fully unravel the spatial variation and geologic control factors of the stress regime of the entire Bavarian Foreland Molasse Basin.
Keywords: North Alpine Foreland Basin; Bavarian Foreland Molasse Basin; Stress regime; Leak-off test; Minimum principal stress

Considering Lithological Variability in Top Seal Analysis. - Drews, Michael; et al. (AAPG Annual Conference, 2014)

Corrigendum to “Disequilibrium compaction overpressure in shales of the Bavarian Foreland Molasse Basin: Results and geographical distribution from velocity-based analyses” [Mar. Pet. Geol. 92 (2018) 37–50](S0264817218300618)(10.1016/j.marpetgeo.2018.02.017) - Drews, Michael; Bauer, Wolfgang; Caracciolo, Luca; Stollhofen, Harald (Marine and Petroleum Geology, 2019)
The authors regret that the following mistakes in the description and graphical representation of the normal compaction trend (NCT) have been erroneously carried forward by the authors from an earlier version of the manuscript to the final version of the manuscript, which does not allow for reproduction of the normal compaction trend used in the study: 1. For all pressure analyses conducted in the study, the constant exponent n of equation (3) has been set to 2.0, instead of 2.19. Therefore, paragraph 1 on page 41 should be read as “[…] which we set to a value of 2.0 for shale, similar to Issler (1992).”2. The vertical stress, necessary to calculate the NCT as represented in Figs. 4, 5 and 6, has been erroneously calculated with a phi0-parameter of 0.35 instead of 0.3 (compare equation (2) and table 1). For the three green data points (Oligocene Normal Pressure, NW-Molasse) of Fig. 5 we spotted an additional minor error in the calculation routine of the vertical effective stress. We attached the corrected figures to the end of this corrigendum.We would like to emphasize that the errors have not been carried forward in the remainder of the study and manuscript. The corrections are only necessary to being able to reproduce the used normal compaction trend, but do not affect any of the results, conclusions or any other figures or written passages of the manuscript. The authors would like to apologize for any inconvenience caused. [Figure presented] Fig. 4. Shale velocities vs. true vertical depth (TVD) for normally pressured Oligocene (yellow and green dots) and Mesozoic shales (blue dots). Oligocene shales from wells in the north-western Bavarian Foreland Molasse Basin (wells marked by green dotted envelope on the map inset and green dots on the velocity-depth plot) generally have faster velocities, which might be attributed to more heterolithic sequences and/or increased uplift. The calculated normal compaction trend (NCT) derived from the combination of the modified Athy equation and the porosity-velocity transform of Raiga-Clemenceau et al. (1988) is represented by the black dashed line. [Figure presented] Fig. 5. Vertical effective stress vs. shale velocity relationship from both normally pressured and overpressured wells. Vertical effective stress values have been derived from drill stem and production tests and wireline formation pressure tests and associated shale velocities are captured from sonic and VSP data from adjacent shale sequences. The dashed black curve represents the normal compaction trend (NCT) established for the Bavarian Foreland Molasse Basin. [Figure presented] Fig. 6. Shale velocities compiled from seismic (VSP) and sonic velocities vs. true vertical depth (TVD) for both normally pressured and overpressured Oligocene and Mesozoic (Cretaceous and Jurassic) shales. Velocities from overpressured Oligocene and Cretaceous shales clearly depart from the normal compaction trend around 2500 m, with some minor diversions even in shallower sections.
CRIS-Team Scopus Importer:2019-12-03

Determination of effective flow properties of caprocks in the presence of multi-scale heterogeneous flow elements - Ma, Jingsheng; Drews, Michael; Kurtev, Kuncho; Aplin, Andrew (International Petroleum Technology Conference 2013: Challenging Technology and Economic Limits to Meet the Global Energy Demand, IPTC 2013, 2013)

Digital outcrop models as input for geostatistical fracture networks simulations - Drews, Michael; Deckert, Hagen (Society of Petroleum Engineers, 2011)

Disequilibrium compaction overpressure in shales of the Bavarian Foreland Molasse Basin: Results and geographical distribution from velocity-based analyses - Drews, Michael; Bauer, Wolfgang; Caracciolo, Luca; Stollhofen, Harald (Marine and Petroleum Geology, 2018)
<span style="color: rgb(46, 46, 46); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 16px; word-spacing: -1.24453px;">Shale velocity data from sonic logs and vertical seismic profiles, drilling data and <em style="border: 0px; font-size: 16px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; color: rgb(46, 46, 46); word-spacing: -1.24453px;">in situ<span style="color: rgb(46, 46, 46); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 16px; word-spacing: -1.24453px;">pressure measurements from a total of 116 wells have been analyzed to gain an improved understanding of the lateral and vertical distribution and formation of overpressure in the Bavarian Foreland Molasse Basin. Pore pressure from sonic and vertical seismic profile velocities has been analyzed by establishing a normal compaction trend for Cenozoic and Mesozoic shales combined with a classical Eaton approach. The study demonstrates that a single shale normal compaction trend for the Bavarian Foreland Molasse Basin is sufficient to estimate pore pressure and thus overpressure from sonic and vertical seismic profile velocity. Maximum overpressure develops at depths between 1500 and 2500 m and increases with depth at a constant effective stress of 20 MPa. The strong dependency of overpressure on burial depth, constant effective stress and restriction to shale units that are overlain by sequences with very high sedimentation rates indicates that disequilibrium compaction is the main cause for overpressure. Also, variable presence of Cretaceous shales is a key control of overpressure occurrence in Oligocene shales in the Bavarian Foreland Molasse Basin, since Cretaceous shales likely act as a “pressure buffer” to underpressured Mesozoic carbonates. Successful detection and prediction of overpressure from vertical seismic profile data is encouraging for future pre-drill prediction of overpressure from velocity data of seismic surveys in the Bavarian Foreland Molasse Basin, resulting in improved well planning, reliable calculation of project costs, and improved safety during drilling activities in the Bavarian Foreland Molasse Basin. The presented overpressure distributions will be a key input for future geomechanical, basin and reservoir modelling studies in the Bavarian Foreland Molasse Basin.
Keywords: North Alpine Foreland Basin; Bavarian Foreland Molasse Basin; Overpressure; Pore pressure; Seismic velocity; Shale

Enhancing seal quality prediction by modelling spatial permeability distributions of meter-scale fine-grained sediments. - Drews, Michael; Kurtev, Kuncho; Böker, Ulf; Ma, Jingsheng; Aplin, Andrew; et al. (Geological Society Meeting: Modelling Sedimentary Basins and their Petroleum Systems, 2010)

Feasibility Study of Future (Hypothetical) Scientific and Geothermal Wells in Franconia, Germany. - Drews, Michael; Bauer, Wolfgang; Stollhofen, Harald (Der Geothermie Kongress DGK 2017, 2017)

„Frankenalb-Malm“: Versenkungsgeschichte zur Kalibrierung eines Molassebecken-Aufschlußanalogs - Freitag, Simon; Drews, Michael; Bauer, Wolfgang; Stollhofen, Harald (DGMK Tagungsbericht 2018-1, 2018)
Mit der Suche nach alternativen Energieformen steigt auch wieder das Interesse an der Nutzung der tiefen Erdwärme. Mehrere Geothermie-Anlagen im Molassebecken sind bereits in Betrieb, wobei die meisten davon die geklüfteten Malm-Karbonate als Ziel-Reservoir angebohrt haben. Für ein verbessertes Systemverständnis dieses Reservoirs werden häufig Analog-Aufschlüsse auf der Fränkischen Alb herangezogen, da die im Molassebecken versenkten Karbonate hier an der Oberfläche austreten. Jedoch ist es bei der Verwendung von Reservoir-Analogen von großer Bedeutung, welche Versenkungsgeschichte die jeweiligen Gesteine erfahren haben, denn dies kann einen entscheidenden Einfluss auf die petrophysikalischen Eigenschaften der Aufschlussanaloge haben. Die Versenkungsgeschichte wurde für die Fränkische Alb bisher kaum untersucht. Ziel der vorliegenden Studie ist es die Versenkungsgeschichte mit Hilfe verschiedener Untersuchungsmethoden an den den Malm unterliegenden Dogger- und Lias-Tonen zu bestimmen. Dazu werden Methoden wie die Vitrinit-Reflexion sowie der Vergleich von Kompaktionstrends aus Bohrungen aus dem Bayerischen Molassebecken und Literaturdaten herangezogen. Verwendet werden dafür sowohl Tone, welche aus aktiven und stillgelegten Tongruben entnommen wurden, als auch Lias- und Dogger-Tone aus flachen Bohrungen. Erste Analysen der Gruben-Tone weisen bei einem Vergleich der Kompaktionstrends mit Bohrdaten aus dem Molassebecken eine Versenkungstiefe von ca. 500-1000 m auf. Diese Tiefenangabe ist jedoch erst eine grobe Einschätzung der tatsächlichen erfahrenen Versenkungstiefe, ein Abgleich mit den beschriebenen Messmethoden wird im nächsten Projektschritt durchgeführt.<br
Keywords: Fränkische Alb; Tonkompaktion; Versenkungsgeschichte

Influence of shale and mudstone heterogeneity on permeability-driven fluid flow - Sample to geophysical well log scale - Drews, Michael; Kurtev, Kuncho; Ma, Jingsheng; Böker, Ulf; Aplin, Andrew (75th European Association of Geoscientists and Engineers Conference and Exhibition 2013 Incorporating SPE EUROPEC 2013: Changing Frontiers, 2013)

Leaky top seals - Evidence, rates and mechanisms - Kurtev, Kuncho; Böker, Ulf; Drews, Michael; Abrakasa, Selegha; Aplin, Andrew (3rd International Conference on Fault and Top Seals: From Characterization to Modelling, 2012)

Metre-scale effective flow properties of heterogeneous fine-grained sediments - Kurtev, Kuncho; Drews, Michael; Ma, Jingsheng; Aplin, Andrew (EAGE Shale Workshop 2010: Shale - Resource and Challenge, 2010)

MINERALOGICAL, BIB-SEM AND PETROPHYSICAL DATA IN SEAL ROCK ANALYSIS: A CASE STUDY FROM THE VIENNA BASIN, AUSTRIA - Misch, D.; Siedl, W.; Drews, Michael; Liu, B.; Klaver, J.; Pupp, M.; Sachsenhofer, R. F. (Journal of Petroleum Geology, 2021)
The Vienna Basin is a major hydrocarbon province with a long exploration history. Within the basin, secondary migration from Upper Jurassic source rocks into stacked Middle Miocene (Badenian) sandstone reservoirs was formerly considered to have occurred almost entirely along major fault zones. However recent exploration data has suggested that in areas where no major faults are present, oil may have migrated vertically through the sandy mudstone intervals separating individual reservoir units, which are therefore imperfectly sealed. In order to investigate possible secondary migration through the semi-permeable mudstones, this study links variations in gross depositional environment (GDE) to variations in mudstone properties (e.g. mineralogy and pore size distribution). The study focussed on the mudstones which seal reservoir sandstones referred to locally as the “8.TH” and “16.TH” units. The bulk mineralogical composition of 56 mudstone and sandy mudstone (and minor intercalated muddy sandstone) samples from seal layers in 22 wells was studied by X-ray diffraction analysis, broad ion beam – scanning electron microscopy (BIB-SEM), mercury intrusion porosimetry (MICP) and N2 adsorption. These data are interpreted in the context of GDE maps of the Vienna Basin which were previously established using seismic and well log data. Results indicate that the gross depositional environment strongly controlled the pore space characteristics of the mudstones. The sandy mudstones in the NW part of the study area were influenced by a complex eastward-prograding deltaic system which deposited coarse detritus into a major palaeo depression (“Zistersdorf Depression”) located in the centre of the basin. Higher overall porosity and a dominance of larger pore size classes, probably resulting in reduced seal quality, were observed for sandy mudstones from well locations within feeder channels and also from within the Zistersdorf Depression. Similarly, sandy mudstones from locations associated with the long-term input of coarser sediments in shoreline, coastal and proximal offshore settings in the NW and central parts of the study area are considered to be of lower sealing quality compared to fine-grained mudstones deposited in distal, open-marine settings which prevailed in the SE part of the study area throughout the Middle Miocene. In general, pore geometries were influenced by mineralogical composition; quartz- and detrital carbonate-rich samples show equidimensional pores, while more elongated pores (with a higher average aspect ratio) characterize clay-rich samples. Furthermore, matrix mesopores (2-50 nm) determined by N2 sorption are more abundant in clay-rich versus quartz-rich samples, and show a pronounced positive trend with increasing percentage of illite-smectite mixed-layer clay minerals. This study shows that regional-scale mudstone seals in the Vienna Basin have been influenced by variations in sedimentation associated with lateral variations in gross depositional environment during the Middle Miocene. The observed pore characteristics will serve as input data for future models of secondary migration.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Austria; BIB-SEM; cap rocks; gas adsorption; hydrocarbon migration; MICP; Miocene; sandstone reservoirs.; seal capacity; Vienna Basin

Modelling spatial permeability distributions in fine-grained sediments on a meter scale - Drews, Michael; Kurtev, Kuncho; Ma, Jingsheng; Aplin, Andrew; et al. (6th IMA Conference on Modelling Permeable Rocks, 2010)

Oberflächennah bis kilometertief – Lehre und Forschung zur Geothermie an der FAU Erlangen - Stollhofen, Harald; Bauer, Wolfgang; Bertermann, David; Drews, Michael; Fazlikhani, Hamed (Geothermische Energie, 2018)
Geothermie-Forschung am GeoZentrum Nordbayern (GZN) der Friedrich-Alexander-Universität (FAU) ist auf die integrierte fazielle, petrographische, petrophysikalische und geomechanische Charakterisierung von Reservoirgesteinen und deren Exploration ausgerichtet. Zudem werden pedologische bzw. geophysikalische Systemzusammenhänge im Bereich der oberflächennahen Geothermie analysiert. Ein neuer Masterstudiengang "GeoThermie/GeoEnergie" zielt auf die Vermittlung eines ganzheitlichen Systemverständnisses.

Overpressure Prediction and its implications for well planning in the Bavarian Foreland Molasse Basin. - Drews, Michael; Bauer, Wolfgang (Praxisforum Geothermie.Bayern 2017, 2017)

PHREASIM: a computer-aided expert system to characterize horizontal fluid flow in and around wells PHREASIM – Ein Expertensystem zur Simulation von Fließverhältnissen in Grundwassermessstellen und deren unmittelbarem Nahfeld - Drews, Michael; et al. (Grundwasser, 2015)
Keywords: Groundwater flow; In-hole flow; Navier-Stokes-Brinkman; PHREASIM; Well flow simulation

Porenüberdruck im Bayerischen Molassebecken - Drews, Michael; Bauer, Wolfgang; Stollhofen, Harald (Erdoel Erdgas Kohle/EKEP, 2018)

Porenüberdruck im Bayerischen Molassebecken - Drews, Michael; Bauer, Wolfgang; Stollhofen, Harald (DGMK Tagungsbericht 2018-April, 2018)

PPFG prediction in complex tectonic settings: The North Alpine thrust front and foreland basin, SE Germany - Drews, Michael; Stollhofen, Harald (2nd EAGE Workshop on Pore Pressure Prediction, 2019)
Estimation of pore and fracture pressures in complex tectonic settings, such as fold-and-thrust belts and their adjacent foreland basins, is usually challenging and often requires local calibration. The Cenozoic North Alpine Thrust Front and Foreland Basin in SE Germany provide an interesting and challenging example for such a complex system, comprising overpressured sections in the thrust belt, the overthrusted foreland sediments below the main detachment and the undeformed foreland basin. Based on the synthesis of recent research in the study area and new analyses of additional well data from the thrust front, pore and fracture pressure models will be presented for the different parts of the North Alpine Thrust Front and Foreland Basin in SE Germany. The results demonstrate, that understanding of the geological history, stress regime variations and overpressure generation are key to estimate pore and fracture pressures in complex tectonic settings, such as the North Alpine Thrust Front and Foreland Basin in SE Germany.
CRIS-Team Scopus Importer:2019-06-21

Quantitative Fracture Set Characterization. - Drews, Michael; Deckert, Hagen; et al. (Geotectonic Research 96/01 – Special Issue TSK 13 Abstracts, 2010)

Reentering of an overpressured basin - The south German Molasse - Drews, Michael; Bauer, Wolfgang; Stollhofen, Harald (1st EAGE Workshop on Pore Pressure Prediction: At the Well Scale from Today to Tomorrow, State of the Art, Recent Progress and Technology Gap, 2017)

Spatially referenced 3D-Characterisation of Fracture Networks - Drews, Michael; Deckert, Hagen; Gessner, Klaus; et al. (Conference Proceedings, 2007)

Sub log-scale heterogeneity of fine-grained sediments - Implications for effective permeability and top seal risking - Drews, Michael; Aplin, Andrew; Kurtev, Kuncho; Ma, Jingsheng (2nd International Fault and Top Seals Conference: From Pore to Basin Scale, 2009)

Ursachenforschung zur geothermischen Anomalie in Nordbayern - Drews, Michael; Bauer, Wolfgang; Fazlikhani, Hamed; Stollhofen, Harald; Kämmlein, Marion; Potten, Martin; Thuro, Kurosch; de Wall, Helga (Geothermische Energie, 2019)